Performing the Sentence. Research and Teaching in Performative Arts - Dertnig, Carola; Thun-Hohenstein, Felicitas (Publication Series of the Academy of Fine Arts Vienna, 2014)
Performing the Sentence brings into dialogue the ways that "performative thinking" has developed in different national and institutional contexts, within different disciplines in the arts, and the conditions under which it has devel- oped in experimental art schools. The anthology collects 21 essays and conversations that weave in and out of the two key areas of research and teaching within performative fine art. They bring to light the conventions involved in the production, presentation, reception and historicization of performance art, as well as the specific cultural and political implications. The various contributions also show how these conventions are produced through or within each artwork, independent from their specific contexts, offering ways of thinking beyond their usual frames of reference. At the same time they recognize the substantial work carried out by artists, critics, and theorists who have built the meanings, references, and implications since the beginning of the "performative turn."